(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Biosurfactants are surface-active compounds produced by a wide variety of diverse microorganisms. The structural diversity of biosurfactants depends on microorganisms and growth conditions (such as substrate and pH). The unique structure of biosurfactants provides unique properties for specific applications. Biosurfactant production still needs to be explored using a variety of microorganisms and growth conditions for producing the diversity of biosurfactant structures. Production and characterization of biosurfactant by Lactobacillus lactis using Crude Palm Oil (CPO) as an additional carbon source has been conducted. The optimization condition of biosurfactant production by L. lactis using media containing various concentrations of CPO was evaluated. Optical density, surface tension, and emulsification index were observed daily for 12 days. Optimal biosurfactant production condition was achieved when L. lactis was grown on media Nutrient Broth containing 10% (v/v) of CPO and incubated for 8 days. Biosurfactants were obtained for 80 mg/L media. Based on Thin Layer Chromatography (TLC) analysis and Fourier Transform Infra-Red (FT-IR) Spectroscopy, produced biosurfactant was identified as a glycolipid biosurfactant containing functional groups of hydroxyl, ester, carboxylic, methyl, and methylene. Produced biosurfactants exhibited the Critical Micelle Concentration (CMC) value of 1 g/L with a surface tension value of 49.46 mN/m. The emulsion system of produced biosurfactant was water in oil (w/o). The produced biosurfactant showed an emulsification index of 41-71% with soybean oil, palm oil, sunflower oil, olive oil, and lubricant oil. The stable emulsion was reached up to 30 days when soybean oil, olive oil, and lubricant oil were used as the water-immiscible compound.